Associations of Prenatal Growth with Metabolic Syndrome, Insulin Resistance, and Nutritional Status in Chilean Children. (15th June 2014) - Mardones, Francisco; Arnaiz, Pilar; Pacheco, Paz; Dominguez, Angelica; Villarroel, Luis; Eriksson, Johan G.; Barja, Salesa; Farías, Marcelo; Castillo, Oscar
Abstract : Introduction . The association of prenatal growth with nutritional status, metabolic syndrome (MS), and insulin resistance (IR) was studied in school-age children. Methods . A retrospective cohort study was designed linking present data of children with perinatal records. 3325 subjects were enrolled. Anthropometry, blood pressure (BP), and pubertal status were assessed. Blood lipids, glucose, and insulin were measured. Linear associations were assessed using the Cochran-Armitage test. Odds ratios and nonlinear associations were computed. Results . 3290 children (52% females, mean age of 11.4 ± 1 years) were analyzed. Prevalence of obesity, stunting, MS, and IR was 16.0%, 3.6%, 7.3%, and 25.5%, respectively. The strongest positive association was between birth weight (BW) and obesity (OR 2.97 (95% CI 2.01–4.40) at BW ≥ 4, 000 g compared to BW 2, 500–2, 999). The strongest inverse association was between birth length (BL) and stunting (OR 8.70 (95% CI 3.66–20.67) at BL < 48 cm compared to BL 52-53 cm). A U-shaped association between BL and BP ≥ 90th percentile was observed. Significant ORs were also found for MS and IR. Adjustments for present fat mass increased or maintained the most prenatal growth influences. Conclusions . Prenatal growth influences MS, IR, and nutritional status. Prenatal growth was more important than present body composition in determining these outcomes.